The proteome microenvironment determines the protective effect of preconditioning in cisplatin-induced acute kidney injury - Späth, Martin Richard; Sáez Rodríguez, Julio (Kidney international, 2019)
Acute kidney injury (AKI) leads to significant morbidity and mortality; unfortunately, strategies to prevent or treat AKI are lacking. In recent years, several preconditioning protocols have been shown to be effective in inducing organ protection in rodent models. Here, we characterized two of these interventions—caloric restriction and hypoxic preconditioning—in a mouse model of cisplatin-induced AKI and investigated the underlying mechanisms by acquisition of multi-layered omic data (transcriptome, proteome, N-degradome) and functional parameters in the same animals. Both preconditioning protocols markedly ameliorated cisplatin-induced loss of kidney function, and caloric restriction also induced lipid synthesis. Bioinformatic analysis revealed mRNA-independent proteome alterations affecting the extracellular space, mitochondria, and transporters. Interestingly, our analyses revealed a strong dissociation of protein and RNA expression after cisplatin treatment that showed a strong correlation with the degree of damage. N-degradomic analysis revealed that most posttranscriptional changes were determined by arginine-specific proteolytic processing. This included a characteristic cisplatin-activated complement signature that was prevented by preconditioning. Amyloid and acute-phase proteins within the cortical parenchyma showed a similar response. Extensive analysis of disease-associated molecular patterns suggested that transcription-independent deposition of amyloid P-component serum protein may be a key component in the microenvironmental contribution to kidney damage. This proof-of-principle study provides new insights into the pathogenesis of cisplatin-induced AKI and the molecular mechanisms underlying organ protection by correlating phenotypic and multi-layered omics data.
published online 3 December 2018
Gesehen am 03.04.2019